Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Pegawai yang Dimediasi Keterlibatan Kerja di Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Semarang - Nurul So’imah; Alimuddin Rival Rivai (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to determine and analyze the Effect of Workload and Job Stress on Employee Performance Mediated by Work Engagement at the Center for Vocational Training and Productivity (BBPVP) Semarang. The population is all employees at BBPVP Semarang, who have civil servant status in 2024 totaling 133 people. The sampling method uses the census or saturation method. The data analysis technique uses SPSS. The results of the study stated that workload has been proven to have a positive and significant effect on work engagement. Work stress shows a positive and significant effect on work engagement. Workload has a positive and significant effect on improving performance. Work stress has a positive and significant effect on performance. And, work engagement is able to mediate the effect of workload and work stress on employee performance.